Lithotripsy of Different Urinary Tract Stones by Using Seeds of Carum copticum - Ahmed G. Sabar (College of Pharmacy University of Baghdad, 2017)
It has been a well-known practice to use seeds and the essential oil of Carum copticum as a strongly  antiseptic ,  antispasmodic ,  aromatic  , bitter ,  diaphoretic  ,  digestive  ,  diuretic , expectorant  and tonic. Also used for cure influenza, asthma, and rheumatoid arthritis. To our knowledge it will be the first time to use the seeds of this herb as a urinary tract stone lithotripsy.This research aimed to the use of these seeds as a lithotripsian against different types of urinary stones and determine the efficiency of these preparation against which types of stone.A liquid solution was prepared from dissolving the seeds powder in cow milk and then concentration this preparation was done by boiling at 100Â°C to reduce the volume of solution to the half.The treatment was given via oral administration for successive 9 days before breakfast. 350 patients with urinary stone of different type took part in this research. All patients were subjected to ultrasonography and intravenous pyelography examinations to localized the position and detect diameter of stone. The above examination and also biochemical tests for diagnosis of stones ingredients were repeated after the administration of treatment and excretion of stone fragments in urine. The results were so promising especially against pure ca-oxalate stone. Key words: Carum copticum; Lithotripsy; Ca-Oxalate stone; mixed stone